Pelatihan dan Pendampingan Program Pembelajaran Individual di Sekolah Dasar Inklusif - Septi Dariyatul Aini; Ukhti Raudhatul Jannah; Ubaidi Ubaidi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
Inclusive education requires learning services that accommodate the diverse characteristics and needs of students, including children with special needs. One approach that can support this objective is the Individualized Learning Program (ILP). However, the implementation of ILP in schools often encounters challenges, particularly related to teachers’ competencies in designing and implementing learning tools tailored to students’ individual needs. This community service program aimed to enhance teachers’ competencies in designing, implementing, and evaluating Individualized Learning Programs at SDN Pademawu Timur 5 Pamekasan. The program was conducted through several stages, including needs assessment, socialization, training and mentoring, program implementation, monitoring, and evaluation. The outputs of the program consisted of individualized teaching modules, diagnostic, formative, and summative assessment instruments, as well as learning media adapted to students’ characteristics. The results indicated significant improvements in teachers’ understanding and skills in developing and implementing ILP-based learning tools. Furthermore, the implementation of the program positively affected students’ learning motivation, active participation, and social interaction. Therefore, training and mentoring on Individualized Learning Programs can serve as an effective strategy to improve the quality of inclusive education and optimize learning services for students with special needs in inclusive elementary schools.